Strategi Kampanye Produk Lokal Indonesia dalam Membangun Kesadaran Merek - Raina Desiana Prafitri; Maman Chatamallah (Bandung Conference Series: Public Relations, 2023)
Abstract. Brand awareness is the main point in introducing a brand, especially with local brand. Currenly, Indonesian local brand are starting to develop and competitive in their competition, this requires a variety of appropriate marketing communication strategies. This things needed to build brand awareness of related products as well as to build attention from potential customers. Erigo, one of the local brand from Indonesia, a retail business engaged in fashion, has recently become the talk of internet users because one of its marketing strategies is through a campaign by placing an advertisements in New York downtown. Advertising is one of the digital marketing strategies that serves to attract the attention of potential consumers through information on products and services offered to stick in the mind of consumers. In addition to advertising, Erigo also has a series of other campaign events, such as introducting its products through New York Fashion Week 2022. This campaign is published through social media platforms such as Instagram and YouTube through KOL. This study aims to determine the local brand campaign strategy of Indonesia in building brand awareness as measured by Integrated Marketing Communication (IMC) theory. The method used in this research is a qualitative method with a case study approach. Data collection techniques in the form of interviews, observations, and literature to strengthen the existing data. The result of this research that Erigo has succeeded in increasing brand awareness and product sales significantly. According to available data and evaluation, it can be said that Erigo will reimplement this campaign in the following next year. With significant result, this campaign strategy was found to be effective in increasing brand awareness and sales for Erigo. Abstrak. Brand Awareness merupakan point utama dalam pengenalan suatu brand terlebih dengan local brand. Saat ini local brand Indonesia mulai berkembang dan kompetitif dalam persaingannya, hal ini memerlukan beragam strategi komunikasi pemasaran yang tepat, hal ini diperlukan untuk membangun brand awareness atas produk terkait sekaligus membangun perhatian dari para calon konsumen. Salah satu brand lokal dari Indonesia yakni Erigo, sebuah bisnis retail yang bergerak di bidang fashion belum lama ini menjadi perbincangan para pengguna internet karena salah satu strategi pemasarannya melalui kampanye dengan memasang iklan di pusat kota New York. Iklan menjadi salah satu strategi pemasaran digital yang berfungsi menarik perhatian calon konsumen lewat informasi produk dan jasa yang ditawarkan agar melekat di benak konsumen. Selain memasang iklan, Erigo juga memiliki rangkaian acara kampanye lainnya seperti memperkenalkan produknya melalui New York Fashion Week 2022. Kampanye ini dipublikasikan melalui platform media sosial Instagram dan YouTube melalui KOL. Penelitian ini bertujuan untuk mengetahui strategi kampanye local brand Indonesia dalam membangun brand awareness yang diukur dengan Teori Integrated Marketing Communication (IMC). Metode yang digunakan dalam penelitian ini dengan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data berupa wawancara, observasi, dan kepustakaan untuk memperkuat data yang ada. Hasil penelitian ini berupa Erigo berhasil meningkatkan brand awareness dan penjualan produk yang signifikan. Menurut data dan evaluasi yang ada, dapat dituturkan bahwa Erigo akan melaksanakan kemabali kampanye ini di tahun berikutnya. Dengan adanya hasil yang signifikan, strategi kampanye ini di rasa efektif untuk meningkatkan kesadaran merek dan penjualan bagi Erigo